y=-3x+8

y=-5x-2

Expert Answers

An illustration of the letter 'A' in a speech bubbles

We can use the substitution method to solve for the solution of the given equations.

if we substitute `y=-3x+8` to the equation `y=-5x-2` , we get

`y=-5x-2`

`(-3x+8)=-5x-2`

`-3x+5x=-2-8`

`2x=-10`

`x=-5`

Then if we substitute the value of x in either of the two equation. Let's say at `y=-3x+8` . We obtain

`y=-3(-5)+8`

`y=15+8`

`y=23`

In other words, the point `(-5,23)` is a solution or intersection of the graphs of the two functions.

See eNotes Ad-Free

Start your 48-hour free trial to get access to more than 30,000 additional guides and more than 350,000 Homework Help questions answered by our experts.

Get 48 Hours Free Access
Approved by eNotes Editorial